Transcriptome Analysis of Small Molecule–Mediated Astrocyte-to-Neuron Reprogramming - Ma, Ning-Xin; Yin, Jiu-Chao; Chen, Gong (Frontiers in Cell and Developmental Biology, 2019)
Chemical reprogramming of astrocytes into neurons represents a promising approach to regenerate new neurons for brain repair, but the underlying mechanisms driving this trans-differentiation process are not well understood. We have recently identified four small molecules-CHIR99021, DAPT, LDN193189 and SB431542-that can efficiently reprogram cultured human fetal astrocytes into functional neurons. Here we employ the next generation of RNA-sequencing technology to investigate the transcriptome changes during the astrocyte-to-neuron conversion process. We found that the four small molecules can rapidly activate the hedgehog signaling pathway while downregulate many glial genes such as FN1 and MYL9 within 24 hours of treatment. Chemical reprogramming is mediated by several waves of differential gene expression, including upregulation of hedgehog, Wnt/ -catenin, and Notch signaling pathways, together with downregulation of TGF- and JAK/STAT signaling pathways. Our gene network analyses reveal many well-connected hub genes such as RGMA, neuronatin (NNAT), neurogenin 2 (NEUROG2), NPTX2, MOXD1, JAG1, and GAP43, which may coordinate the chemical reprogramming process. Together, these findings provide critical insights into the molecular cascades triggered by a combination of small molecules that eventually leads to chemical conversion of astrocytes into neurons.